Aberrant Scinderin Expression Correlates With Liver Metastasis and Poor Prognosis in Colorectal Cancer - Qi Lin; Jun Li; Dexiang Zhu; Zhengchuan Niu; Xiangou Pan; Pingping Xu; Meiling Ji; Ye Wei; Jianmin Xu (Frontiers Media S.A., 2019)
Many genes and mutations have been reported for colorectal cancer (CRC); however, very few have been associated with colorectal cancer liver metastasis (CRLM). We performed gene expression profiling experiments to identify genetic markers for CRLM and elucidate the molecular mechanisms. Microarray experiments were performed on CRC primary tumor samples with or without liver metastasis (LM) using the Affymetrix U133 plus 2.0 GeneChip Array. A new identified gene-scinderin (SCIN) was overexpressed with synchronous LM at both the RNA level evaluated with quantitative real-time PCR and protein level evaluated with immunohistochemistry and also with short overall survival analyzed with Kaplan-Meier method. With multivariate analysis indicated that SCIN served as an independent poor prognostic predictor for CRC patients. Disease-free survival was also significantly lower in SCIN overexpressing CRC patients with metachronous LM. In addition, SCIN knockdown significantly reduced cell proliferation, induced cell cycle arrest, and promoted the expression of some cell cycle apoptosis-related protein. Moreover, the DIAPH1, STAT3, CDK2, CDK4, and EGFR levels were downregulated, whereas CDKN2B and COL4A1 were upregulated in DLD-1-shSCIN cells by microarray analysis compared with DLD-1 shCon cells. These findings revealed that SCIN may serve as an important predictor of CRLM and poor outcome for CRC patients. SCIN may be a potential therapeutic target in human CRC. However, translation of its roles into clinical practice will require further investigation and additional experimental validation.